Phenolic Screening and Total Phenolic Content of Jelutung Rawa (Dyera polyphylla (Miq.) Steenis) Plant Extracts - Febriani, Melda; Muharini, Rini; Mayasari, Eni; Ola, Antonius (Jurnal Kimia Riset, 2025)
Dyera polyphylla (Miq.) Steenis, or jelutung rawa, is an endemic tree species native to Indonesia’s tropical peat swamp forests. While related species such as Dyera costulata have been reported to contain various bioactive compounds particularly phenolics with antioxidant, anti-inflammatory, and antimicrobial properties, there has not been phytochemical studies on D. polyphylla. This study aimed to investigate the phenolic compound profile and total phenolic content in the stem wood, stem bark, and leaves of D. polyphylla. Extraction was carried out using total and stratified maceration methods with n-hexane, ethyl acetate, and methanol as solvents. Qualitative analysis involved phytochemical screening by using phenolic specific reagents, thin-layer chromatography (TLC) with FeCl₃ reagents, and high-performance liquid chromatography (HPLC). Total phenolic content was quantified using the Folin–Ciocalteu spectrophotometric method. Phenolic compounds were detected in all plant parts, particularly in the ethyl acetate and methanol extracts. HPLC analysis showed that the chromatographic profile of the methanol extract from stem wood closely resembled that of the leaves. The highest phenolic content was observed in the methanol extract of the leaves (29.02 mg GAE/g). These results suggested that D. polyphylla, particularly its leaves, is a promising natural source of phenolic compounds with potential antioxidant and therapeutic value.